TPL‐2 kinase induces phagosome acidification to promote macrophage killing of bacteria. (21st April 2021) - Breyer, Felix; Härtlova, Anetta; Thurston, Teresa; Flynn, Helen R; Chakravarty, Probir; Janzen, Julia; Peltier, Julien; Heunis, Tiaan; Snijders, Ambrosius P; Trost, Matthias; Ley, Steven C
Abstract: Tumour progression locus 2 (TPL‐2) kinase mediates Toll‐like receptor (TLR) activation of ERK1/2 and p38α MAP kinases in myeloid cells to modulate expression of key cytokines in innate immunity. This study identified a novel MAP kinase‐independent regulatory function for TPL‐2 in phagosome maturation, an essential process for killing of phagocytosed microbes. TPL‐2 catalytic activity was demonstrated to induce phagosome acidification and proteolysis in primary mouse and human macrophages following uptake of latex beads. Quantitative proteomics revealed that blocking TPL‐2 catalytic activity significantly altered the protein composition of phagosomes, particularly reducing the abundance of V‐ATPase proton pump subunits. Furthermore, TPL‐2 stimulated the phosphorylation of DMXL1, a regulator of V‐ATPases, to induce V‐ATPase assembly and phagosome acidification. Consistent with these results, TPL‐2 catalytic activity was required for phagosome acidification and the efficient killing of Staphylococcus aureus and Citrobacter rodentium following phagocytic uptake by macrophages. TPL‐2 therefore controls innate immune responses of macrophages to bacteria via V‐ATPase induction of phagosome maturation. Synopsis: TPL‐2 kinase plays an important role in innate immune responses to bacteria, mediating Toll‐like receptor (TLR) activation of ERK1/2 and p38α MAP kinases in myeloid cells. Here, TPL‐2 is shown to also directly promote macrophage bacterial killing by MAP kinase‐independent induction of phagosome maturation. TPL‐2 catalytic activity is required for phagosome acidification in macrophages following uptake of latex beads. TPL‐2 induces phagosome acidification independently of MAP kinase activation. TPL‐2 induces phagosome acidification by promoting phosphorylation of DMXL1, a V‐ATPase‐associated protein. TPL‐2 induces phagosome acidification and bacterial killing following internalization of Staphylococcus aureus or Citrobacter rodentium by macrophages. Abstract : In addition to the well‐established role of TPL‐2 in regulating cytokine expression in response to TLR signaling, TPL‐2 also regulates phagosome maturation via the V‐ATPase to control a bacterial infection.